Use of modern educational technologies in vocational education classes - Karimova, Maftuna; Khimmatov, Mekhroj (MMIT Proceedings, 2024)
In this article, several modern, interactive pedagogical methods for students in education, their advantages, disadvantages and differences from each other are briefly discussed.